Randomized double blind crossover trial of Aloe vera , Cnidoscolus chayamansa and placebo for reducing hyperglycemia in women with early metabolic syndrome - Cárdenas Ibarra, Lilia; Villarreal Pérez, Jesús Zacarías; Lira Castillo, J. Carlos; Nava Alemán, Aram (Elsevier Health Sciences, 2017)
Background: There have been antidiabetic claims for Aloe vera (AG) Barbadensis Mill. gel and infusion of Cnidoscolus chayamansa (CC) McVaugh. Objectives: To determine if the ingestion of total process AG concentrated 5:1 (TA), AG, CC or placebo can reduce hyperglycemia in women with early metabolic syndrome (EMS). Methods: One hundred-twenty five women from two outpatient university clinics were randomly assigned to a three assay doubleblind crossover procedure. Subjects were adult women with EMS by ATP III criteria assigned to assay 1: AG&CC vs P1&P2; assay 2: AG&P2 vs P1&CC; or assay 3: TA vs P3. All assays included the ingestion of one, then zero (washout period), then two gelatins/day, for 4, 1, 4 weeks, respectively. The expected outcome was an HbA1c decrease ≥4.2 mmol/mol or lower but sustaining euglycemia. Results: Participants had a mean age of 46.8 ± 9.7 years and a mean HbA1c of 47.8 ± 12.7 mmol/mol at the start of the study. The least tolerated combination was AG&P2. Patients complained of bad taste and mild stomach pain because of the double dose of this treatment; this caused withdrawals: 4/25 vs. 9/21, respectively, Chi square ¼ 4.1, df ¼ 1, P < 0.05. Changes in HbA1c (mmol/mol) were assay 1, 1.8 ± 7.5 vs 1.6 ± 6.9, P > 0.05; assay 2, 1.3 ± 6.6 vs 1.4 ± 7.6, P > 0.05; assay 3, 4.9 ± 8.3 vs 0.44 ± 5.4, P < 0.01, respectively. TA concomitantly reduced high-sensitive C-reactive protein (hs-CRP) (P < 0.05). Conclusions: Data suggest that TA decreases blood glucose levels by reducing the proinflammatory state. The infusion of microwave dehydrated CC leaves did not reduce blood glucose or HDL and triglyceride levels.